Developing science and technology – the role of Big Tech - Bruno Damásio; Sandro Mendonça; Eduardo Silva (International Telecommunications Society (ITS), 2023)
This work aims to conduct a scientometric study on the research published by digital platforms known as Big Tech (Amazon, Apple, Facebook, Google and Netflix), giving an overview of the publications' growth, distribution by document's types, research themes and affiliations' profile. All data was retrieved from the Scopus' database, only publications in English and that had an associated DOI (digital object identifier) were considered. Given Big Tech's financial and development strategies, they are present in many markets outside their core activity, enabling them to be at the forefront in innovation. Hence, Big Tech invest in research related activities such as scientific publishing, showing a great surge in their levels of publications from 2015 onwards. "Computer Science" is the most popular journal subject area in which they tend to publish. In the publications' authorship there were no outstanding international partnerships found, with the Big Tech companies' researchers being the main authors, nonetheless a propensity to work with universities was identified. These results help to profile Big Tech's research activity,
Keywords: 330; Big Tech; research; scientometric; publication; digital platforms